Generalizations of Ranamujanas Results In Terms Of q-Product Identities (Global Journal of Science Frontier Research, 2012)
In this paper author has generalized Ramanujan's results and established four new relations on q-product identities with the help of Jacobi's triple product identity using elementary method.
Keywords: Triple product identities; q-product identities